sj-docx-3-sjp-10.1177_14034948221075016 – Supplemental material for Internet-delivered cognitive behavioral therapy (iCBT) for common mental disorders and subsequent sickness absence: a systematic review and meta-analysis - Lina Udd-granat (12050451); Jouni Lahti (591654); Michael Donnelly (3470117); Charlene Treanor (4819374); Sami P. Pirkola (12050454); Tea Lallukka (2993499); Anne Kouvonen (152505) (2022)
Supplemental material, sj-docx-3-sjp-10.1177_14034948221075016 for Internet-delivered cognitive behavioral therapy (iCBT) for common mental disorders and subsequent sickness absence: a systematic review and meta-analysis by Lina Udd-granat, Jouni Lahti, Michael Donnelly, Charlene Treanor, Sami P. Pirkola, Tea Lallukka and Anne Kouvonen in Scandinavian Journal of Public Health